Answer:
x = 5, x = 4
Explanation:
Oh I love these!!
3x + 8 + 2x = -3(x-16)
First, distribute the -3 across the parentheses. -3(x-16)
3x + 8 + 2x = -3x + 48
Next, let's add 3x and 2x on the left side of the equation there to clean it up a bit and give us less numbers to work with. 3x + 2x
8 + 5x = -3x + 48
Let's take the opportunity to add -3x on both sides so we can get all of the algebraic expressions containing (x) on one side.
8 + 8x = 48
Subtract 8 on both sides.
8x = 40
Divide by 8 to finally isolate x!
x = 5
Second one let's go!
0.5(6x - 4) = 2x - 6x + 26
Similar to the first equation, we'll need to distribute the 0.5 across the parentheses first. 0.5(6x - 4)
3x - 2 = 2x - 6x + 26
To clean the equation up let's subtract 6x from 2x on the right side of the equation there.
3x - 2 = -4x + 26
Add 2 to both sides.
3x = -4x + 28
Isolate the algebraic expressions that hold our x variables captive. (Add -4x to both sides.)
7x = 28
Divide by 7 on both sides to isolate x.
x = 4